Does (Non‐)Meaningful Sensori‐Motor Engagement Promote Learning With Animated Physical Systems?. Issue 2 (11th July 2016) - Pouw, Wim T. J. L.; Eielts, Charly; van Gog, Tamara; Zwaan, Rolf A.; Paas, Fred
ABSTRACT: Previous research indicates that sensori‐motor experience with physical systems can have a positive effect on learning. However, it is not clear whether this effect is caused by mere bodily engagement or the intrinsically meaningful information that such interaction affords in performing the learning task. We investigated ( N  = 74), through the use of a Wii Balance Board, whether different forms of physical engagement that was either meaningfully, non‐meaningfully, or minimally related to the learning content would be beneficial (or detrimental) to learning about the workings of seesaws from instructional animations. The results were inconclusive, indicating that motoric competency on lever problem solving did not significantly differ between conditions, nor were response speed and transfer performance affected. These findings suggest that adult's implicit and explicit knowledge about physical systems is stable and not easily affected by (contradictory) sensori‐motor experiences. Implications for embodied learning are discussed.